Oral stepdown in Gram‐positive bloodstream infections: A step in the right direction. Issue 3 (18th February 2023) - Caniff, Kaylee E.; Rebold, Nicholas; Rybak, Michael J.
Abstract: Bloodstream infections (BSIs) due to Gram‐positive organisms have traditionally been treated with prolonged courses of intravenous antimicrobials. However, this dogma is associated with substantial burden to the patient and health care system. Consequently, there is growing interest in the utilization of oral stepdown therapy, defined as the transition of intravenous therapy to an active oral agent, for this indication. This review highlights available literature examining oral stepdown in adult patients with BSI due to commonly encountered Gram‐positive pathogens, including Staphylococcus aureus, Streptococcus spp., and Enterococcus spp. Support for oral stepdown in this setting is primarily derived from observational studies subject to selection bias. Nevertheless, this treatment strategy exhibits promising potential in carefully selected patients as it is consistently associated with reductions in hospital length of stay without jeopardizing clinical cure or survivability. Prospective, randomized trials are needed for validation of oral stepdown in Gram‐positive BSI and to identify the optimal patient population and regimen.